Impairment of glucose-induced insulin secretion in human pancreatic islets transplanted to diabetic nude mice. - Jansson, L (1995)
Hyperglycemia-induced beta-cell dysfunction may be an important component in the pathogenesis of non-insulin-dependent diabetes mellitus. However, most available data in this field were obtained from rodent islets. To investigate the relevance of this hypothesis for human beta-cells in vivo, human pancreatic islets were transplanted under the renal capsule of nude mice. Experimental groups were chosen so that grafted islets were exposed to either hyper- or normoglycemia or combinations of these for 4 or 6 wk. Grafts of normoglycemic recipients responded with an increased insulin release to a glucose stimulus during perfusion, whereas grafts of hyperglycemic recipients failed to respond to glucose. The insulin content of the grafts in the latter groups was only 10% of those observed in controls. Recipients initially hyperglycemic (4 wk), followed by 2 wk of normoglycemia regained a normal graft insulin content, but a decreased insulin response to glucose remained. No ultrastructural signs of beta-cell damage were observed, with the exception of increased glycogen deposits in animals hyperglycemic at the time of killing. It is concluded that prolonged exposure to a diabetic environment induces a long-term secretory defect in human beta-cells, which is not dependent on the size of the islet insulin stores.